Mechanical properties of hybrid honeycomb sandwich structure having facesheets reinforced with flax, kenaf and glass fibers - Ashraf, Waqas (2022)
The honeycomb sandwich structures are consisted of two thin facesheets and a thick honeycomb core. The commercially available sandwich structures used in aircraft interiors are based on synthetic fiber composite facesheet but have limitations like recycling, non-biodegradability and disposal problems. These factors push the need for environmentally friendly materials. From the literature review, it has been identified that the studies reported on the natural fiber-based composite facesheet with a honeycomb core are minimal. In this research, a new class of sandwich structures with glass fiber and natural fiber like flax and kenaf composite facesheet has been fabricated using the pre-cure fabrication technique. Two layers of the epoxy adhesive film sheet were used each to bond the top and bottom pre-cured facesheets with an aluminium honeycomb core. The mechanical properties of the sandwich structure specimens under various loads (Tensile, edgewise compression, and flexural) with respect to the fiber stacking sequence and natural fiber treatment were studied. The peel strength was measured through the climbing drum peel test to analyze the facesheet and core bonding strength. The lowvelocity impact behavior was analyzed by the drop weight impact test, and the residual strength of the impacted specimen was characterized through the bending test. Among the studied configurations, the glass composite facesheet revealed the highest mechanical performance than the natural composite facesheet. However, the compression strength and flexural stiffness of the natural fiber were improved when they were combined with synthetic material by around 38% and 66 % in flax/glass hybrid and 52% and 83% in kenaf/glass hybrid facesheet, respectively, compared to their non-hybrid composite. The mechanical performance of the sandwich structure was further enhanced by around 7% to 15 % when alkali-treated natural fibers were used in a hybrid combination. Overall, the hybrid combination, which has glass in the outer layer, showed better mechanical performance than stacking it in the middle. The flax/glass hybrid composite facesheet exhibited competitive performance by achieving 96% edgewise compression, 92% flexural facing stress, and 94 % flexural stiffness of the sandwich structure having a glass composite facesheet. The drum peel strength revealed the competitive strength by using the pre-cure method of sandwich structure fabrication. The low-velocity impact results revealed that the hybrid composite facesheet showed promising results compared to the glass composite sandwich structure. The hybrid composite sandwich structure showed more penetration of the impactor, resulting in better energy absorption by around 5% to 18 % than the glass composite. The glass and both hybrid facesheet combinations exhibited similar residual bending performance when results were compared with their counter non-impacted specimens. Based on the findings in this work, the results showed the potential of using hybrid reinforcement to improve the structural performance compared to non-hybrid flax and non-hybrid kenaf composite and revealed the promising and comparable structural performance compared with pure glass composite facesheet. The sandwich structure with hybrid composite facesheet sandwich structure can substitute existing sandwich structures in aerospace and ground transportation such as railways and the automobile sector with the benefit of low cost, low density, and low environmental impact.